2005
DOI: 10.1136/jcp.2004.022707
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the novel quantitative ARMS assay and an enriched PCR–ASO assay for K-rasmutations with conventional cytology on endobiliary brush cytology from 312 consecutive extrahepatic biliary stenoses

Abstract: Background: Extrahepatic biliary stenosis (EBS) has malignant and benign causes. Patients with EBS are at risk of having or developing malignancy. Accurate diagnostic tests for early detection and surveillance are needed. The sensitivity of biliary cytology for malignancy is low. K-ras mutation analysis on brush cytology is a valuable adjunct, but specificity is low. A quantitative test for K-ras mutations has been developed: the amplification refractory mutation system (ARMS). Aim: To assess the test characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…Previous reports suggest that KRAS mutation analysis can be used to detect cancer in pancreatobiliary tract brushings, 10,22 bile fluids, 9,23 and fine needle aspirates from pancreatic masses. 8,24 Comparisons of KRAS mutation analysis to conventional cytology have generally shown that KRAS mutation analysis increases sensitivity, but often at the expense of test specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggest that KRAS mutation analysis can be used to detect cancer in pancreatobiliary tract brushings, 10,22 bile fluids, 9,23 and fine needle aspirates from pancreatic masses. 8,24 Comparisons of KRAS mutation analysis to conventional cytology have generally shown that KRAS mutation analysis increases sensitivity, but often at the expense of test specificity.…”
Section: Discussionmentioning
confidence: 99%
“…However, a sensitive assay has been developed that can quantify not just the presence but also the levels of mutant KRAS in blood and pancreatic juice, and it remains possible that this quantification of mutant KRAS levels could improve the diagnostic utility of KRAS as an end point in pancreatic cancer (13). In addition, the addition of KRAS mutation detection may improve the diagnostic accuracy of brush cytology done in extrahepatic biliary obstruction (14).…”
Section: Pancreatic Tumor Tissuementioning
confidence: 99%
“…Lièvre and colleagues [Lievre et al 2006] reported for the first time that KRAS codon 12 and 13 mutations predict resistance to cetuximab in a series of 30 mCRC patients. Last year, the same authors [Lievre et al 2008] [Simi et al 2008]; amplification refractory mutation system (ARMS) [Van Heek et al 2005], and new technologies such as pyrosequencing are under development [Ogino et al 2005].…”
Section: Kras Mutations Assessment: Clinical Evidence and Technical Imentioning
confidence: 99%